Upfront Magnetic Resonance Imaging-Guided Stereotactic Laser-Ablation in Newly Diagnosed Glioblastoma: A Multicenter Review of Survival Outcomes Compared to a Matched Cohort of Biopsy-Only Patients. Issue 6 (23rd November 2018) - Mohammadi, Alireza M; Sharma, Mayur; Beaumont, Thomas L; Juarez, Kevin O; Kemeny, Hanna; Dechant, Cosette; Seas, Andreas; Sarmey, Nehaw; Lee, Bryan S; Jia, Xuefei; Fecci, Peter E; Baehring, Joachim; et al.
Abstract: BACKGROUND: Laser ablation (LA) is used as an upfront treatment in patients with deep seated newly diagnosed Glioblastoma (nGBM). OBJECTIVE: To evaluate the outcomes of LA in patients with nGBM and compare them with a matched biopsy-only cohort. METHODS: Twenty-four nGBM patients underwent upfront LA at Cleveland clinic, Washington University in St. Louis, and Yale University (6/2011-12/2014) followed by chemo/radiotherapy. Also, 24 out of 171 nGBM patients with biopsy followed by chemo/radiotherapy were matched based on age (< 70 vs ≥ 70), gender, tumor location (deep vs lobar), and volume (<11 cc vs ≥11 cc). Progression-free survival (PFS), overall survival (OS), and disease-specific PFS and OS were outcome measures. Three prognostic groups were identified based on extent of tumor ablation by thermal-damage-threshold (TDT)-lines. RESULTS: The median tumor volume in LA (n = 24) and biopsy only (n = 24) groups was 9.3 cm 3 and 8.2 cm 3 respectively. Overall, median estimate of OS and PFS in LA cohort was 14.4 and 4.3 mo compared to 15.8 mo and 5.9 mo for biopsy only cohort. On multivariate analysis, favorable TDT-line prognostic groups were associated with lower incidence of disease specific death ( P  = .03) and progression ( P  = .05) compared to other groups including biopsy only cohort. Only age (<70 yr, P  = .02) and tumor volume (<11 cc, P  = .03) were favorable prognostic factors for OS. CONCLUSION: The maximum tumor coverage by LA followed by radiation/chemotherapy is an effective treatment modality in patients with nGBM, compared to biopsy only cohort. The TDT-line prognostic groups were independent predictor of disease specific death and progression after LA.